LITERASI PAJAK, KESADARAN WAJIB PAJAK DAN SISTEM ADMINISTRASI PAJAK MODERN PADA KEPATUHAN WAJIB PAJAK - Anisa Rahma Desi; Adelina Suryati; Iis Dewi Herawati (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2024)
This study aims to examine the effect of tax literacy, taxpayer awareness and modern tax administration system on the compliance of MSME taxpayers in Cibitung and Setu Districts, Bekasi Regency. This research is a quantitative study where the objects used are MSMEs in Cibitung and Setu Districts. This research was conducted using Probability Sampling with random sampling method. The population in this study were all MSMEs in Cibitung and Setu Districts, totalling 1,026. The analytical tool in this study was Smart Pls Version 4.0 and the research instrument used was a questionnaire consisting of a measurement scale of Tax Literacy, Taxpayer Awareness and Modern Tax Administration System on Taxpayer Compliance. Based on the results of the study, it shows that tax literacy, taxpayer awareness, and the tax administration system affect taxpayer compliance. This research is expected to provide a benefit for the Agency (Bekasi Regency Cooperative and UKM Office) to continue to increase counselling to taxpayers to increase understanding of taxation rules so that taxpayers become aware of carrying out their tax obligations and will increase taxpayer compliance